ASUHAN KEPERAWATAN MALARIA DENGAN PENDEKATAN PROSES KEPERAWATAN DI PUSKESMAS MELOLO KABUPATEN SUMBA TIMUR - EMANUEL ILEATAN LEWAR (JURNAL KESEHATAN PRIMER, 2016)
Introduction: Malaria is a parasitic infection of red blood cells caused by a protozoan species of plasmodium transmitted to humans through the saliva through puncture (bite) Anopheles mosquito. Nursing to malaria is a process or series of activities in nursing practice that directly provided to clients who suffer from malaria in various arrangements of health services, using the nursing process approach that includes assessment, determination of nursing diagnosis, planning of nursing, implementation and evaluation, as well as guided by the nursing standards. The purpose of this research is to get an overview of nursing care in patients with malaria. Method : This study used a descriptive method eksploiratif with qualitative approach aimed at understanding the social situation or social phenomena from the standpoint that the informant would get a picture of nursing care in patients with malaria. Result: The results of this study are nurses apply nursing care in patients malaria with the nursing process approach by reviewing, determining nursing diagnoses, nursing planning, implementation and evaluation.Conclusions :Research on malaria nursing care with the nursing process in the Public Health Centers Melolo East District Sumba, can be used as an initial step for nurses in health centers to provide nursing care in a proper malaria.